Association of attenuated mutants of Salmonella enterica serovar Enteritidis with porcine peripheral blood leukocytes - Stepanova, Hana; Volf, Jiri; Malcova, Marcela; Matiasovic, Jan; Faldyna, Martin; Rychlik, Ivan (FEMS microbiology letters, 2011)
In this study, we were interested in the association of attenuated mutants of Salmonella enterica serovar Enteritidis with subpopulations of porcine white blood cells (WBC). The mutants included those with inactivated aroA, phoP, rfaL, rfaG, rfaC and fliC genes and a mutant with five major pathogenicity islands removed (ΔSPI1-5 mutant). Using flow cytometry, we did not observe any difference in the interactions of the wild-type S. Enteritidis, aroA and phoP mutants with WBC. ΔSPI1-5 and fliC mutants had a minor defect in their association with granulocytes and monocytes, but not with T- or B-lymphocytes. All three rfa mutants associated with granulocytes, monocytes and B-lymphocytes more than the wild-type S. Enteritidis did. Electron microscopy confirmed that the association correlated with the intracellular presence of S. Enteritidis and that the Salmonella-containing vacuole in the WBC infected with the rfa mutants, unlike all other strains, did not develop into a spacious phagosome. Intact lipopolysaccharide, but not the type III secretion system encoded by SPI-1, SPI-2 or the flagellar operon, is important for the initial interaction of S. Enteritidis with porcine leukocytes. This information can be used for the design of live Salmonella vaccines preferentially targeting particular cell types including cancer or tumor cells.
Keywords: mutace; Animals; salmonelové vakcíny; Salmonella Vaccines; bakteriální geny; salmonelová infekce u zvířat; prasata; Swine Diseases; Mutation; Glycosyltransferases; Salmonella enteritidis; leukocyty; nemoci prasat; Swine; Leukocytes; glykosyltransferasy; Salmonella Infections, Animal; Genes, Bacterial; zvířata